An Artificial Immune System for Solving Dynamic Economic Power Dispatch Problems - Aragón, Victoria S. (2019)
In this paper, we propose an artificial immune system called IA DED, which stands for Immune Algorithm Dynamic Economic Dispatch. It is designed for solving the Dynamic Economic Dispatch (DED) problem. Our approach considers the DED problem as a dynamic problem whose constraints change over time. IA DED considers the activation process that T cells suffer in order to find partial solutions. The proposed approach is validated using several DED problems taken from the specialized literature. Our results are compared with respect to those obtained by other approaches taken from the specialized literature. We also provide some statistical analysis in order to determine the sensitivity of the performance of our proposed approach to its parameters.